PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE DISCOVERY LEARNING PADA MATERI KONSEP KELILING DAN LUAS BANGUN DATAR SISWA KELAS V A SD NEGERI 009 PULAU KIJANG KECAMATAN RETEH - Mujiati Mujiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this research is the poor student learning outcomes and low awareness of teachers to apply an effective and innovative learning. This study aims to determine whether there is improvement of mathematics learning outcomes before and after the discovery learning method is applied on Grade VA SD Negeri 009 Pulau Kijang Kecamatan Reteh. The number of subject of this research was 22 students consisting of 8 male students and 14 female students with heterogeneous ability. The minimum passing grade, hereinafter KKM and Analysis on Average is used to know whether or not there is enhancement of mathematics learning outcomes before and after the discovery model is applied. The research findings reveal that the number of students that achieved the KKM (75) based on the first data obtained from the teacher was 7 (32%). At the first cycle, the number increased to 14 (64%), and at the second cycle, the number increased to 19 (86%). The average score of the student based on the first data obtained from the teacher was 72.7. At the first cycle, the average score increased to 76.3 and at the second cycle, it creased to 82. Referring to the research findings, it can be concluded that the application of the discovery learning method can enhance mathematics learning outcomes of students of Grade VA SD Negeri 009 Pulau Kijang Kecamatan Reteh of 2016.